Employment and the National Dividend - Taussig, F. W. (Quarterly Journal of Economics, 1936)
Journal Article Employment and the National Dividend Get access F. W. Taussig F. W. Taussig Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 51, Issue 1, November 1936, Pages 198–203, https://doi.org/10.2307/1882508 Published: 01 November 1936